Sustainable Supply Chain Management Practices in Batik Small and Medium Scale Enterprises Performance - Syukron, Hikmaturrizqi Amalia; Solovida, Grace Tianna (Universitas Dian Nuswantoro Semarang, 2022)
The research was conducted to analyze the relationship between sustainable supply chain management practices and the performance of environmentally friendly batik SMEs. The concept of Sustainable Supply Chain Management has become the right choice for business activities. Eco-friendly batik SMEs must be responsible for environmental practices and social practices in the scope of internal and external management and their impact on all dimensions of corporate sustainability performance. The research sample was 70 owners of environmentally friendly batik SMEs in several cities in Central Java and Yogyakarta. Data analysis was performed through Partial Least Squares (PLS). The general conclusion of this research was that internal management and external management influenced corporate performance. However, supplier assessment and supervision and supplier collaboration did not influence corporate performance. Keywords: internal management, external management, SME performance, MRPB, Triple Bottom Line, Eco-friendly batik UKM